Multi-platform metagenomic characterization of the microbial community during spontaneous cacao fermentation - Joel Tigrero-Vaca; Mirian Villavicencio-Vásquez; Jonathan Coronel; Juan Manuel Cevallos-Cevallos (Frontiers in Bioengineering and Biotechnology)
Cacao fermentation is a spontaneous process in which microorganisms play a key role in the development of distinctive chocolate flavors. The microbiota acting during cacao fermentation has been routinely characterized by culture-based techniques and next-generation sequencing using Illumina’s platform. However, the potential of in situ sequencing technologies to monitor microbial dynamics during cacao fermentation has not been assessed. In this study, cacao bean samples were collected at 0, 24, 48, 72, and 96 h after the start of the fermentation. Total DNA was extracted, and sequencing libraries were prepared for further sequencing using Illumina’s and Nanopore’s MinION sequencing platforms. Additionally, microorganisms were isolated using traditional culture-based methods. At the order and family taxonomic levels, Illumina and MinION sequencing revealed similar microbial composition in the samples. However, discrepancies were observed at the genus and species levels. In this sense, Illumina sequencing revealed a predominance of Limosilactobacillus, Levilactobacillus, Lactiplantibacillus, Frauteria, Saccharomyces and Acetobacter, while MinION sequencing showed a prevalence of Escherichia, Salmonella, Liquorilactobacillus, Lentilactobacillus, Acetobacter and Komagataeibacter during fermentation. The three methods were consistent in detecting the major yeast (Saccharomyces cerevisiae), lactic acid bacteria (Lactiplantibacillus plantarum, Leuconostoc pseudomesenteroides, Levilactobacillus brevis, Liquorilactobacillus mali, and Lentilactobacillus hilgardii) and acetic acid bacteria (Acetobacter pasteurianus) species during fermentation. Functional analysis based on a hybrid assembly of Illumina and MinION data revealed the roles of lactic acid bacteria and acetic acid bacteria in the metabolism of carbohydrates, amino acids, and secondary metabolites such as polyphenols and theobromine. This study represents the first report assessing the applicability of MinION sequencing for the characterization of microbial populations during cacao fermentation, demonstrating its potential as a complementary tool to established sequencing platforms.